Efektifitas Pembelajaran Berbasis Inquiry Melalui Implementasi Modeling Instruction pada Materi Alat Optik - Soekarman Soekarman (Universitas Pendidikan Mandalika, 2021)
This study aims to analyze inquiry-based learning through the implementation of modeling instruction on optical instrument materials. This research method used quantitative descriptive research. The subjects of this study were students of class XI IPA SMAN 2 Donggo. The collection technique includes observation, literature review, questionnaire, test and documentation. The data obtained will be analyzed descriptively quantitatively, among the research data to be analyzed are: student activities, learning outcomes, and student responses to ongoing learning. The results of this study include: 1) Student activity obtained a score of 74.58% or good category, 2) Inquiry learning with Modeling Instruction on optical instrument material can actually improve students' understanding with an N-gain score of 1.3 points or very high category. high, 3) Student responses to learning obtained a score of 84.37% or very interesting category. Based on the results of the study, it was found that through Inquiry learning with Modeling Instruction on Optical Instruments material, it can be used as an alternative to improve the quality of learning in class, especially in Physics subjects.